Physical and physiological determinants of rock climbing - MacKenzie, R.; Monaghan, L.; Masson, R. A.; Werner, A. K.; Caprez, T. S.; Johnston, L.; Kemi, O. J. (International Journal of Sports Physiology and Performance, 2020)
Climbing has gained in popularity standards, and Olympic recognition, but not the scientific attention that other sports have received. As a sport, climbing takes many forms. For recreational, competitive, and exercise training purposes, sport climbing has evolved as the widest reaching subdiscipline.1 The safe and controlled environment of fixed protection (bolts or topropes) of sport climbing allows a full focus on athletic and gymnastic challenges,2,3 and as such, it is characterized by sustained, repetitive, and complex bouts of intense upward motion that tax physical capacity in the upper limbs and upper and core body.4,5 Growth of indoor facilities has further facilitated this trend.1